Сутнісні характеристики формування готовності фахівців фізичного виховання і спорту до використання методики кінезіотейпування - Рибалко, П. Ф.; Rybalko, P. F.; Русин, Л. П.; Rusyn, L. P.; Шанта, І. Ф.; Shanta, I. F.; Титович, А. О.; Tytovych, A. O.; Лазоренко, С. С.; Lazorenko, S. S.; Хацаюк, О. В.; Khatsaiuk, O. V.; et al. (Науковий часопис НПУ імені М. П. Драгоманова. Серія 5: Педагогічні науки: реалії та перспективи. - 2021. - Вип. 82. - С. 127-133, 2021)
Визначено сутнісні характеристики формування готовності тренерів (фахівців фізичного виховання і спорту), що спеціалізуються в одноборствах, до використання методики кінезіотейпування у системі багаторічної підготовки спортсменів: це особистісне утворення, що формується засобами цілеспрямованого та акцентованого педагогічного впливу на формування у тренерів (фахівців фізичного виховання і спорту) готовності до швидкого відновлення спортсменів на різних етапах фізичної терапії (ерготерапії) після травм, хвороб опорно-рухового апарату тощо з використанням сучасних методик кінезіологічного тейпування, а також до організації системи багаторічної підготовки атлетів із урахуванням позитивного ефекту сертифікованих аплікаційних стрічок. Така готовність тренера забезпечує узгодження ним знань про зміст і структуру професійної тренерської діяльності, вимог до рівня володіння методикою кінезіологічного тейпування різних частин тіла спортсмена на етапі його фізичної терапії, сформованих компетентностей до організації навчально-тренувального процесу, а також змагальної діяльності зі сформованими та усвідомленими ним під час професійного розвитку можливостями і потребами.

Given the fact that the training and competitive activities of athletes may be suspended for a certain period due to their injury, the urgency of organizing appropriate measures of physical therapy and occupational therapy, which will ensure their accelerated recovery. in accordance with the above, there is a need to develop and implement in the educational process of future coaches, as well as a system of advanced training of existing coaches (specialists in physical training and sports) applied methods of physical therapy (occupational therapy), which involve the use of kinesiological taping. the main purpose of the work is to determine the essence and structure of the formation of the readiness of coaches (specialists in physical education and sports) to use the technique of kinesiotaping in the system of long-term training of athletes who specialize in martial arts. as a result of theoretical research, members of the research group determined the essential characteristics of the readiness of coaches (specialists in physical education and sports) who specialize in martial arts to use the technique of kinesiotaping in the system of long-term training of athletes – personal education, which is formed by means of purposeful and accentuated pedagogical influence on the formation of coaches (specialists in physical education and sports) readiness for rapid recovery of athletes at different stages of physical therapy (occupational therapy) after injuries, diseases of the musculoskeletal system, etc., using modern methods of kinesiological taping, to organize a system of long-term training of athletes taking into account the positive effect of certified application tapes and ensures their coordination of knowledge about the content and structure of professional coaching activities, as well as the requirements of this activity to the level of kinesiological taping of different parts of the athlete, formed competencies for the organization of the educational and training process, as well as competitive activities with the opportunities and needs formed and realized by him in the process of professional development. prospects for further research in the chosen area of scientific research include determining the criteria and levels of readiness of specialists in physical education and sports (for example, coaches specializing in martial arts) to use the technique of kinesiological taping in professional activities.

Определены сущностные характеристики формирования готовности тренеров (специалистов физического воспитания и спорта), специализирующихся в единоборствах, к использованию методики кинезиотейпирования в системе многолетней подготовки спортсменов: это личностное образование, формируемое средствами целенаправленного и акцентированного педагогического воздействия на формирование у тренеров (специалистов спорта) готовности к быстрому восстановлению спортсменов на разных этапах физической терапии (эрготерапии) после травм, болезней опорно-двигательного аппарата и т.п. с использованием современных методик кинезиологического тейпирования, а также организации системы многолетней подготовки атлетов с учетом положительного эффекта сертифицированных аппликационных лент. Такая готовность тренера обеспечивает согласование им знаний о содержании и структуре профессиональной тренерской деятельности, требований к уровню владения методикой кинезиологического тейпирования различных частей тела спортсмена на этапе его физической терапии, сформированных компетентностей к организации учебно-тренировочного процесса, а также соревновательной деятельности со сформированными и осознанными им при профессиональном развитии возможностями и потребностями.
Essential characteristics of the formation of the readiness of physical education and sport specialists to use the technique of kinesiotaping in professional activities
Рибалко, П. Ф. Сутнісні характеристики формування готовності фахівців фізичного виховання і спорту до використання методики кінезіотейпування / Рибалко П. Ф., Русин Л. П., Шанта І. Ф. та ін. // Науковий часопис НПУ імені М. П. Драгоманова. Серія 5: Педагогічні науки: реалії та перспективи. - 2021. - Вип. 82. - С. 127-133. -DOI: https://doi.org/10.31392/NPU-nc.series5.2021.82.27.
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Фізична культура. Спорт. Physical Education. Sport. Физическая культура. Спорт; освітній процес; educational process; образовательный процесс; педагогічне моделювання; pedagogical modeling; педагогическое моделирование; тренери; trainers; тренеры; фізичне виховання; physical education; физическое воспитание; кінезіологічне тейпування; kinesiological taping; кинезиологическое тейпирование; фізична терапія; physical therapy; физическая терапия; готовність; readiness; готовность